Implementasi Kurikulum Merdeka Belajar terhadap Peningkatan Kinerja Guru di SD Negeri 1 Rejosari Natar Kabupaten Lampung Selatan - Ratih May Sinta; Mashdaria Huwaina; Khoironi Khoironi (Journal on Education, 2024)
The curriculum is the "spirit" of education which must be innovative, dynamic and periodic in accordance with developments over time and science and technology, the competencies required by society and users of graduates. The Merdeka Curriculum was designed as an effort by the Ministry of Education, Culture and Research and Technology to overcome the learning crisis that we have been facing for a long time, and which is getting worse due to the Covid 19 pandemic. Then this crisis is characterized by low student learning outcomes, even in basic things such as reading literacy. One of the determining factors for the success of implementing learning activities is the teacher. Therefore, teachers must understand the curriculum comprehensively, starting from theoretical concepts to its implementation in the classroom. Therefore, this article describes the implementation of the Independent Learning Curriculum to improve teacher performance at SDN 1 Rejosari. This research uses a qualitative approach, in collecting data using participant observation, documentation studies, and interviews. The results of this research consist of: (1) Learning planning for the Independent Learning Curriculum (2) Implementation of the Independent Curriculum (3) Implementation of their Curriculum towards Improving Teacher Performance (4) Evaluation of the Implementation of the Independent Learning Curriculum for the implementation of the Independent Curriculum at SDN 1 Rejosari Natar, South Lampung Regency by carrying out learning in accordance with the teaching module and evaluating learning using submative and formative assessment processes.